Analisis Pengaruh Entrepreneurial Networking Dan Keuanggulan Bersaing Terhadap Kinerja Usaha Dengan Pemanfaatan Digital Marketing Sebagai Pemoderasi Pada Umkm Kota Medan - Gaol, Masria Lumban; Sigalingging, Eni Duwita (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2022)
The objective of the research was to find out 1) the influence of Entrepreneurial Networking, Competitive Advantage on MSME Business Perfomance in Medan, and 2) Digital Marketing in modernizing the influence of Entrepreneurial Networking, Competitive Advantage on MSME Business Perfomance in Medan, The population used causality method. The population was 85 MSME in Medan Amplas, and all of them were used as the samples and analyzed by using measurement model (outer model) and structural model (inner model), and effect size for moderating variable. The result of the research showed that 1) Entrepreneurial Networking, Competitive Advantage Â had positive and significant influence on MSME Business Perfomance in Medan, and 2) Digital Marketing could moderate the influence of Entrepreneurial Networking, Competitive on MSME Business Perfomance in Medan.Â